Another perspective on the high uninsured-rate in the USA: Crowding out of long term health insurance by the institutional setting of the U.S. health insurance system - Ines Läufer (Otto-Wolff-Institut für Wirtschaftsordnung (owiwo), 2014)
In the USA, previous to the implementation of the Affordable Care Act, about 50 million people under 65 years didnt have any (private or public) health insurance. A lot of them have been temporally insured via an employer sponsored group insurance. Because of the linkage to the job, group insurance does only provide an incomplete protection against long term health costs. Alternatively, an individual guaranteed renewable contract allows for long term protection. This paper considers the possible options of a young, still good risk person. A person who is a high risk today could have been a healthy and low-risk person in the past. This article analyses essential factors explaining the attractiveness of group insurance compared to an individual long term contract. If the group insurance goes along with the abandonment of long term contracts, it can contribute to a high level of temporarily non-insured persons. As the price gap between employer-sponsored group insurance and individual guaranteed renewable contracts is partly state-induced, non-insurance can also be the result of a state-induced crowding-out of long term protection.
Keywords: I11; I13; I18; 330; Krankenversicherung; Betriebliche Sozialleistungen; Private Krankenversicherung; Steuervergünstigung; Verdrängungseffekt; Versicherungsschutz; Dauer; USA